A tale of two belongings: social and academic belonging differentially shape academic and psychological outcomes among university students - Lawrie, Smaranda Ioana; Carter, Delwin B.; Nylund-Gibson, Karen; Kim, Heejung S. (Frontiers in Psychology, 2025)
The benefits of belonging in academic settings are well established; however, past empirical research has for the most part conflated academic and social belonging. This study utilized latent class analysis (LCA) with a sample of undergraduates (N = 837) to determine whether distinct classes or profiles of belonging exist on a college campus and whether class membership predicts academic and psychological outcomes. Four distinct belonging classes emerged: High Social, High Academic belonging (35%), Low Social, High Academic belonging (15%), High Social, Low Academic belonging (38%), and Low Social, Low Academic belonging (12%). The results show that belonging classes play different roles. For academic outcomes (GPA), academic belonging was important, but not social belonging. For psychological outcomes (stress and self-esteem), both academic and social belonging mattered but academic belonging mattered more. These findings demonstrate that investigating the distinctive roles of academic and social belonging is a fruitful theoretical and applied endeavor.